2013
DOI: 10.1155/2013/762303
|View full text |Cite
|
Sign up to set email alerts
|

Site-Specific Distribution of CD68-Positive Microglial Cells in the Brains of Human Midterm Fetuses: A Topographical Relationship with Growing Axons

Abstract: Using 5 fetuses of gestational age (GA) of 15-16 weeks and 4 of GA of 22–25 weeks, we examined site- and stage-dependent differences in CD68-positive microglial cell distribution in human fetal brains. CD68 positive cells were evident in the floor of the fourth ventricle and the pons and olive at 15-16 weeks, accumulating in and around the hippocampus at 22–25 weeks. At both stages, the accumulation of these cells was evident around the optic tract and the anterior limb of the internal capsule. When we compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…F, upper panel). Moreover, costaining of P2Y 12 and CD68 confirmed the strong expression of this glycoprotein on clustered microglia as described previously (Cho et al, ), whereas nonclustered microglia of the same fetus were characterized by moderate CD68 immunoreactivity (Fig. F, middle panel).…”
Section: Resultssupporting
confidence: 86%
“…F, upper panel). Moreover, costaining of P2Y 12 and CD68 confirmed the strong expression of this glycoprotein on clustered microglia as described previously (Cho et al, ), whereas nonclustered microglia of the same fetus were characterized by moderate CD68 immunoreactivity (Fig. F, middle panel).…”
Section: Resultssupporting
confidence: 86%
“…Further adding to this diversity, a subset of the latter population additionally expressed CD68 (~35%) and/or isolectin B 4 (~15%) in the OB (Ribeiro Xavier et al , ). Significantly increased CD68 expression in microglia was also reported in the OB of adult wild‐type rats (Doorn et al , ), while a regional distribution of CD68‐positive microglia was reported in the brain of human midterm fetuses (gestational ages of 15–25 weeks; Cho et al , ). As observed in the SVZ and RMS, IBA1‐negative and IBA1‐positive microglia were also observed in close vicinity to another within the OB.…”
Section: Introductionmentioning
confidence: 78%
“…Furthermore, microglia support neurogenesis, neuronal survival, and the maintenance and maturation of oligodendrocyte progenitor cells through their release of trophic cytokines, also in the adult brain (Sierra et al, 2010 ; Arnò et al, 2014 ; Hagemeyer et al, 2017 ; Wlodarczyk et al, 2017 ). The positioning of microglial cells along axonal tracts suggests a role in neuronal wiring during embryonic and postnatal stages (Cho et al, 2013 ; Squarzoni et al, 2014 ). From early postnatal development until normal aging, a main contribution of microglia in the healthy brain is their activity-based regulation of neuronal activity and synaptic plasticity, which is notably exerted through the refinement of synaptic connections (Wake et al, 2009 ; Tremblay et al, 2010 ; Bialas and Stevens, 2013 ).…”
Section: Physiological Functions Of Microglia In the Brainmentioning
confidence: 99%